THE ROLE OF CUSTOMER VALUE MEDIATE THE RELATIONSHIP OF MARKETING STRATEGY TO MARKETING PERFORMANCE ON RUBBER FARMERS IN SENTAJO RAYA DISTRICT, KUANTAN SINGINGI REGENCY - Maulia Nur Afifah; Shorea Khaswarina; Yeni Kusumawaty (Agricultural Socio-Economics Journal, 2022)
This study aims to analyze the role of customer value as an intervening variable/mediation of the influence of marketing strategy on the marketing performance of smallholder rubber farmers in Sentajo Raya District, Kuantan Singingi Regency. Sampling in this study was 15% of the population as many as 36 smallholder rubber farmer respondents with each sample must be taken proportionally according to the population in two villages, namely Jalur Patah Village and Parit Teratak Air Hitam Village in Sentajo Raya District. The sampling technique was done by random sampling. The data analysis tool used in this research is SmartPLS 3.0 Sobel test and VAF calculation. The results of this study indicate that the customer value variable cannot mediate the relationship between market strategy and marketing performance. While the customer value variable can mediate the relationship of marketing mix strategy to marketing performance where the role of the mediating effect of customer value is partial mediation of 0.540 or 54.0%.